(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A Project is a group of people who have a common purpose or objective.A Project usually comprises several undertakings which have to be accomplishedby a certain date, within a given budget with some expected level ofperformance. All Projects have some well-defined objectives and sufficientresources to complete the required tasks and sub-tasks. The basic objective of a Project management is to control the overallProject and maximize the use of the limited resources. For this purpose, a teamis built in Project management in order to increase the efficiency of a Projectand to control the overall activities of a Project. This team includes aProject manager and several Project engineers.